2018 26th European Signal Processing Conference (EUSIPCO) 2018
DOI: 10.23919/eusipco.2018.8553492
|View full text |Cite
|
Sign up to set email alerts
|

Bilinear Residual Neural Network for the Identification and Forecasting of Geophysical Dynamics

Abstract: Due to the increasing availability of large-scale observation and simulation datasets, data-driven representations arise as efficient and relevant computation representations of dynamical systems for a wide range of applications, where modeldriven models based on ordinary differential equation remain the state-of-the-art approaches. In this work, we investigate neural networks (NN) as physically-sound data-driven representations of such systems. Reinterpreting Runge-Kutta methods as graphical models, we consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(111 citation statements)
references
References 20 publications
(20 reference statements)
2
107
0
Order By: Relevance
“…Since the observations are "perfect", DA has not been carried out in this case. The RMSE-f at t 0 + h (see the right-most bar in panel (b)) is 0.014 which is close to the value in Fablet et al (2018) despite the fact that, in our case, the model is not identifiable. If the field is observed with less than 50% coverage, the skills are significantly degraded.…”
Section: Forecast Skillssupporting
confidence: 66%
See 1 more Smart Citation
“…Since the observations are "perfect", DA has not been carried out in this case. The RMSE-f at t 0 + h (see the right-most bar in panel (b)) is 0.014 which is close to the value in Fablet et al (2018) despite the fact that, in our case, the model is not identifiable. If the field is observed with less than 50% coverage, the skills are significantly degraded.…”
Section: Forecast Skillssupporting
confidence: 66%
“…As stated in the introduction, several papers have used convolutional neural networks for representing surrogate models (see, e.g., Shi et al, 2015;de Bezenac et al, 2017;Fablet et al, 2018). Equation (3) being in the incremental form x k+1 = x k + · · · , one-block residual networks are suitable (He et al, 2016).…”
Section: Convolutional Neural Network As Surrogate Modelmentioning
confidence: 99%
“…As opposed to the resolvent, unveiling the flow rate (4) may offer an explicit representation of the model, closer to an ordinary (or partial) differential equation system. This could be efficiently achieved through a simple expansion on monomial regressors [6] or using a NN [45,19,28]. It has been found that NN architectures for the dynamics that mimic numerical integration schemes, and which take the form of residual NNs, are particularly adequate [17,13].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent dynamical system identification techniques [14,15] can be used predict sp,t+1 from sp,t. Natural candidates to learn a parametrization of Φ are recurrent neural networks, such as LSTMs, which are able to handle long term temporal correlations.…”
Section: Neural Network Architectures To Learn Dynamical Systemsmentioning
confidence: 99%